ROLE OF ‘REDUNDANT’ OR ‘PSEUDO’ CLINICAL VIGNETTES IN FORMATIVE ASSESSMENT - P K Rajesh (Asian Journal of Medicine & Health Sciences, 2020)
It is true that though students can escape bad teaching they would still be victims to bad assessment. Assessment based on real life happenings, issues which the student would find themselves during the vocation they are being trained for is the ideal assessment method rendering validity and authenticity. They are also termed as fit for purpose ‘assessment tasks